2003
DOI: 10.1109/tpwrd.2003.817738
|View full text |Cite
|
Sign up to set email alerts
|

Computation of very fast transient overvoltages in transformer windings

Abstract: The algorithm uses a modified continuous Fourier transformation that provides an accurate time domain computation. As an example, the interturn voltage distributions for two 500-kV autotransformers are computed and compared with measurements provided by other publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…σ, μ and d are the conductivity, permeability and the winding coils gap respectively. The details of modeling and the parameters estimation for an inhomogeneous winding (realizing frequency dependent parameters) are discussed in [10].…”
Section: Mtl Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…σ, μ and d are the conductivity, permeability and the winding coils gap respectively. The details of modeling and the parameters estimation for an inhomogeneous winding (realizing frequency dependent parameters) are discussed in [10].…”
Section: Mtl Modelmentioning
confidence: 99%
“…The published works on the machines is more focused on the RLC ladder network model in past [1][2][3][4][5][6]. While the published works on MTL modeling is mostly concentrated on modeling of electrical rotating machines and also on only the homogenous transformer windings ignoring the frequency dependency of the winding insulation parameters [7][8][9][10][11][12]. This paper compares the two well-known MTL and RLC ladder network models and used these models for PD studies in high frequency range 10kHz < f < 5MHz.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-transmission-line (MTL) model has been widely used to model large power transformer windings at high frequency or in a wide frequency range for the analysis of very fast transient overvoltage (VFTO) [1][2][3][4][5] , partial electromagnetic oscillation [6] and partial discharge [7] in the windings. However, there are still some problems to be solved when MTL model is used for large power transformer windings modeling on turn basis.…”
Section: Introductionmentioning
confidence: 99%
“…So far there was significant research done on the investigation of transients in transformers [3][4][5][6][7][8]. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4], the lumped parameter analysis was used for transformer modelling, and [5,6] deal with the modelling of transformer based on the well-known Rabins method. It was also shown that transformer can be modelled by considering the windings or group of windings as transmission lines [7,8]. Furthermore, Wilcox et al [9] proposed a model that can be generally applied for multi-phase multi-winding transformers.…”
Section: Introductionmentioning
confidence: 99%